Study of natural gas storage on activated carbon and MIL-101(cr) blend - Tan, Cheong Heng (2017)
Demands for natural gas have been increasing due to its ability to be a replacement for crude oil and coal for electric power generation, residential heating, industrial and commercial use at lower cost and less harmful environmental effects. A wide range of researches have been conducted to improve the efficiency of storage and application of natural gas. Adsorbed Natural Gas (ANG) allows methane to be stored at room temperature and atmospheric pressure, giving it preference over Liquefied Natural Gas (LNG) and Compressed Natural Gas (CNG) which require extreme low temperature and high pressure respectively. However, extensive research and development is still required for ANG to achieve similar efficiencies as LNG and CNG even at room temperature. Metal Organic Frameworks (MOFs) have proven to be suitable adsorbent candidates attributed to relatively large specific surface area, thermal stability and pore size. The US Department of Energy (DOE) has set a challenging adsorption target for methane storage at 0.5 g/g under ambient conditions, hence the ideal MOF has to be synthesized in order to achieve the target. Adsorption uptake experiments are conducted on four MOF samples namely MIL-101(Cr), K-doped MIL-101(Cr), MIL-101(Cr) + Maxsorb III and MIL-101(Cr) + SiO2 composites using a volumetric and cryogenic experimental set up. The results obtained are compared with previous experimental data in order to investigate their adsorption capabilities for the working temperatures of 125K, 140K, 160K, 180K and 300K. The microstructures of each material sample were analysed using Scanning Electron Microscopy (SEM), BET surface area measurement (BET) and X-ray diffraction (XRD) methods. The experimental results yield that higher gravimetric uptake are achieved at lower temperatures and pressures. However, it is noted that none of the samples were able to achieve the DOE target at ambient condition. The isosteric heat of adsorption of each sample is observed to decrease with increasing gravimetric uptake. The results as presented in this report are suitable for LNG-ANG coupling conditions, where the cold energy is utilized properly.